Acute Macular Neuroretinopathy: An Atypical Hemorrhagic Presentation - Pinto, Christophe (2021)
Acute macular neuroretinopathy (AMN) is a rare disease. We report a clinical case of AMN diagnosed in a 46-year-old, Caucasian female with an atypical exuberant hemorrhagic presenta- tion. She referred unilateral paracentral scotomas started 1 day before admission. Fundoscopy revealed several large, dot-and-blot and flame-shaped intraretinal hemorrhages surrounded by reddish-brown, wedge-shaped lesions pointed towards the fovea. Infrared imaging displayed petalloid dark lesions. Optical coherence tomography showed focal ellipsoid zone disruptions, areas of outer retinal hyperreflectivity and deep intraretinal hemorrhages. Fundus autofluorescence and fluorescein angiography displayed hypofluorescent areas due to intraretinal hemorrhages. One-month after presentation, the patient complained about residual scotomas. Classic reddish-brown, wedge-shaped lesions became well-demarcated and intraretinal hemorrhages almost completely resolved. Tomographic findings partially reversed but converted into outer nuclear layer thinning. Visual field examination displayed paracentral scotomas. Our patient revealed the classic AMN lesions. From our knowledge, this is the first reported AMN case with an extensive hemorrhagic presentation.